(untitled) (Research, Society and Development, 2020)
This article is the result of the experience of nursing professors and academics during a flu vaccination campaign, affected by the H1N1 virus, in the municipalities of Belém and Ananindeua in the state of Pará in the context of the new Covid-19. The experience took place during the first phase of the campaign from 23 to 28 March 2020. The results of this campaign were satisfactory for immunization. In the elderly population, the target was exceeded and reached 101.65% of the priority group. Regarding health professionals, the brand was also higher than expected and reached 91.82% of this audience. With this, this research shows that vaccination against Influenza is a strategy of great importance in order to maximize the diagnosis and the consequent treatment of Covid-19.